Improvement Model for Efficiency in the LPG Bottling Process Using Lean Manufacturing and Industry 4.0 Tools in a Bottling Plant - Méndez-Gutiérrez, Leidy Lucia; Cubas Llanos, Edgar Alexander; Montesinos Ore, Fabricio (LACCEI, 2025)
This study developed an integrated improvement model to optimize operational efficiency in the Liquefied Petroleum Gas (LPG) bottling process by strategically converging Lean Manufacturing tools with enabling Industry 4.0 technologies. The main root causes of reprocessing were identified as recurring failures in the sealing system, excessive idle times, and operational disorganization. To address these issues, the DMAIC methodology was applied to structure a solution based on 5S, Standardized Work, and Total Productive Maintenance (TPM), complemented by IoT sensors that enabled predictive maintenance at critical control points. The model was validated through simulation using SIMIO software, which demonstrated significant improvements: an increase in Overall Equipment Effectiveness (OEE), a 67% reduction in defective products, an 83% decrease in reprocessing, and greater production flow stability. The results show that the synergy between Lean practices and digital technologies enables systemic interventions with high impact on quality, reliability, and productivity. It is concluded that the proposed model is effective, scalable, and replicable, offering a viable alternative for enhancing competitiveness in industrial plants within the energy sector.